1979
DOI: 10.1007/bf00154586
|View full text |Cite
|
Sign up to set email alerts
|

The structure of knowledge and departmental social organization

Abstract: This case study of three university departments was designed to generate substantive theory about decision-making in academic departments. Using Homans' social systems theory as a framework, the theory postulates that the degree of par~/digm development of a discipline affects the extent of interaction in the external and internal systems of its associated departments. The rate of interaction affects the crystallization of norm structures and consequently processes of influence and decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Not only are logical structures and truth criteria tighter in the sciences, physical scientists tend to exhibit more agreement over content but also tighter decision-making processes in the department (Lodahl & Gordon, 1972;Adkinson, 1976). In the Lodahl and Gordon study, however, when professors were asked to judge how much course content would vary among comparable courses in departments in the same discipline, on a scale from 1 (very little) to 10 (a lot), means for physics (3.6) and chemistry (4.7) were not substantially lower than the means for sociology (4.9) and political science (5.8).…”
Section: Between Organizing Principles and Truth Criteriamentioning
confidence: 99%
“…Not only are logical structures and truth criteria tighter in the sciences, physical scientists tend to exhibit more agreement over content but also tighter decision-making processes in the department (Lodahl & Gordon, 1972;Adkinson, 1976). In the Lodahl and Gordon study, however, when professors were asked to judge how much course content would vary among comparable courses in departments in the same discipline, on a scale from 1 (very little) to 10 (a lot), means for physics (3.6) and chemistry (4.7) were not substantially lower than the means for sociology (4.9) and political science (5.8).…”
Section: Between Organizing Principles and Truth Criteriamentioning
confidence: 99%
“…The latter can be penetrated by those students who become teachers and to that extent the progress through BSc and PhD forms an initiation rite into the profession defined by the boundaries of the departmental discipline. An interesting study on how the strength of this boundary is affected by the nature of the discipline is provided by Adkison (1979). Halsey & Trow (1971) draw attention to the power of departments and their professorial heads, and this is strongly confirmed by Moodie & Eustace (1974) who state that "whatever the precise boundaries of departmental autonomy, its existence makes of every university a 'federal' structure rather than a strongly centralised system".…”
Section: The Departmental Ethosmentioning
confidence: 93%
“…Even there, great care is needed. Berg & Ostergren (1977, 1979 have shown that, because of the independence of universities, resistances may be created even by external rewards (see below).…”
Section: Departments Under Threatmentioning
confidence: 97%
See 2 more Smart Citations